2016
DOI: 10.18632/oncotarget.10260
|View full text |Cite
|
Sign up to set email alerts
|

Persistent donor derived Vδ4 T cell clones may improve survival for recurrent T cell acute lymphoblastic leukemia after HSCT and DLI

Abstract: The outcome for T-cell acute lymphoblastic leukemia (T-ALL) in relapse after hematopoietic stem cell transplantation (HSCT) is quite poor, while, both donor lymphocytes infusion (DLI) and adoptively infusion of γδ T cells in leukemia patients after HSCT have demonstrated good results in prolonging survival time of patients. Here, we reported a T-ALL case who experienced three relapses and received HSCT and DLI with an overall survival (OS) time lasting for more than seven years. Based on our previous identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We found that different oligoclonal TRDV subfamily T cells might have unique functions. We found that the clonal expansion patterns of TRDV4 and TRDV8 T cells might be independent protective factors for CR, which is consistent with our previous findings in which we found that clonally expanded TRDV4 T cells might be related to better outcome for a T-ALL patient [19]. We suggested that such expanded TRDV4 and TRDV8 T cell clones might be reactive T cell clones directed against leukemia that serve as biomarkers for the therapeutic efficacy of AML patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that different oligoclonal TRDV subfamily T cells might have unique functions. We found that the clonal expansion patterns of TRDV4 and TRDV8 T cells might be independent protective factors for CR, which is consistent with our previous findings in which we found that clonally expanded TRDV4 T cells might be related to better outcome for a T-ALL patient [19]. We suggested that such expanded TRDV4 and TRDV8 T cell clones might be reactive T cell clones directed against leukemia that serve as biomarkers for the therapeutic efficacy of AML patients.…”
Section: Discussionsupporting
confidence: 91%
“…PCR product analysis produced a single dominant peak or double peaks, which demonstrate a skewed spectratype profile termed “oligoclonality” or “biclonality”, respectively. “Oligoclonality trending” is a classification with a profile between that of polyclonality and oligoclonality [19]. Clonal expansion was detected for all eight TRDV subfamilies in the γδ T cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although hematopoietic stem cell transplantation (HSCT) provides cures in some cases, the 1-year OS following allogeneic (allo) HSCT has reached approximately 30% ( 4 6 ), with the majority of mortality being attributed to disease progression. Despite the poor outcomes with allo-HSCT, ALL has been shown to be responsive to immunotherapy, including donor lymphocyte infusion and adoptive T cell therapy ( 3 , 7 10 ). In fact, ALL is the prototype malignancy for the use of chimeric antigen receptor T cells, highlighting the potential of immunotherapy to eliminate ALL and improve patient outcomes ( 7 9 , 11 ).…”
Section: Introductionmentioning
confidence: 99%